1970
DOI: 10.1126/science.167.3915.192
|View full text |Cite
|
Sign up to set email alerts
|

Bile Pigment Formation in Plants

Abstract: The unicellular alga Cyanidium caldarium evolves carbon monoxide during the syntheis of the bile pigment, phycocyanobilin. Carbon monoxide and phycocyanobilin were produced in stoichiometric amounts at comparable rates. Therefore, the mechanism of bile pigment formation in this plant parallels that in mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1971
1971
1989
1989

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…The ratio of the specific radioactivity of phycoerythrobilin to that of CO synthesized from ALA in P. cruentum cells is what would be predicted if these compounds arose directly from the protoporphyrin IX skeleton of a metalloporphyrin precursor (Table II; experiment II). This conclusion is consistent with the data on specific radioactivity ratios of phycocyanobilin and CO made from ALA-5-4C in cells of the green alga, Cyanidium caldarium (31). It has been observed that metal-free protoporphyrin IX is converted slowly and inefficiently to bile pigment in mammals (7), in contrast to hemoglobin or hematin which are rapidly and quantitatively converted to CO and bilirubin in vivo (2,11) and in vitro (26,27).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The ratio of the specific radioactivity of phycoerythrobilin to that of CO synthesized from ALA in P. cruentum cells is what would be predicted if these compounds arose directly from the protoporphyrin IX skeleton of a metalloporphyrin precursor (Table II; experiment II). This conclusion is consistent with the data on specific radioactivity ratios of phycocyanobilin and CO made from ALA-5-4C in cells of the green alga, Cyanidium caldarium (31). It has been observed that metal-free protoporphyrin IX is converted slowly and inefficiently to bile pigment in mammals (7), in contrast to hemoglobin or hematin which are rapidly and quantitatively converted to CO and bilirubin in vivo (2,11) and in vitro (26,27).…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that the CO evolved by cells of the alga, C. caldarium, was a by-product of phycocyanobilin formation (31). However, the origin of CO produced by other algae and by higher plants has yet to be established.…”
Section: Discussionmentioning
confidence: 99%
“…mmole) were added. Previous results have shown that C. caldarium cells administered ALA-5-"C2 synthesized equimolar quantities of "CO and phycocyanobilin-"C (15). Theoretically, 8 moles of ALA-5-w"C are required for synthesis of 1 mole of heme, which would contain 4 labeled carbon atoms in the pyrrole rings, and 4 labeled carbon atoms in the methyne bridges.…”
Section: Cells In the Lightmentioning
confidence: 98%
“…The specific radioactivity of phycocyanobilin was divided by 7 so it could be compared directly to that of CO. The specific radioactivity of phycocyanobilin was determined from spectral and radiochemical measurements as described previously (15). 1 Represents CO present in the reservoir and in the dead volume of the system consisting of rubber tubing and the gas above the cell suspension in the fermentator tank.…”
Section: Cells In the Lightmentioning
confidence: 99%
See 1 more Smart Citation